KUALITAS PERAIRAN PANTAI DI KABUPATEN BADUNG YANG DIMANFAATKAN SEBAGAI AKTIVITAS PARIWISATA - I Ketut Sundra (Bumi Lestari Journal of Environment, 2011)
Existing beaches in Badung (Kuta, Legian, Nusa Dua, Jimbaran, Tanjung Benoa and Canggu) is a beach full of tourism activities (hotel, restaurant and nautical sports facilities) and other activities. The presence of waste that is not managed well will greatly contribute to the decline in the quality of waters. Results of analysis by in-situ and laboratory in the wet season and dry in 2008 and 2009 ie from 19 parameters analyzed physic, chemical and microbiological, there is 8 parameters has exceeded the maximum threshold for designation as a marine tourism in accordance with Governor’s Rule of Bali No. 7 in 2007. Seawater quality parameters that exceed the Environmental Quality Standards is DO, BOD5, NO3, NH3, phenol, phosphate, cadmium (Cd) and Plumbum (Pb). The results on the quality of coastal waters are four beaches (Kuta, Legian, Nusa Dua and Jimbaran) are classified as low polluted, and two beaches (Tanjung Benoa and Canggu) is classified as middle polluted. The research concluded that in general the water quality at six beaches in Badung in 2008 and 2009 is still worth utilized for the purposes of maritime tourism.